Ambientes de Realidade Virtual direcionados para a Educação Patrimonial: um Estudo de Caso aplicado na Virtualização do Museu de Arqueologia da UFMS - Carlos Henrique da Costa Silva (2023)
With the advancement of Virtual Reality technologies, several institutions and companies are exploring new concepts to enrich their daily activities and develop new products. In this context, museums have also sought technological innovations to provide differentiated experiences for visitors. Thinking about the potential application of Virtual Reality and museums' search for new technologies, this work aimed to create virtual visiting environments aimed at museums, with the UFMS Archeology Museum as a case study. To develop these virtual environments, web development tools were used, such as VueJS, A-Frame and Strapi. The combination of these technologies allowed the construction of immersive virtual environments, enabling visitors to explore the museum and its collections virtually. Through these technologies, open source-based software was developed, which runs directly on the web and can be conveniently accessed on different devices. In this way, the software had the mission of democratizing access to culture and promoting Heritage Education, breaking down geographic and socioeconomic barriers, which often affect the population in a comprehensive way. What's more, the software can be used as an educational tool aimed at transforming the conventional approach to teaching and enriching the learning experience of students. With this in mind, it can be said that the software in question provides a solution to the needs of the case study, opening the way for new possibilities for applying Virtual Reality in museums and other cultural institutions.